Total Mikroba pada Tanah yang Dicemari Sludge Limbah Pabrik Kertas dengan Perlakuan Pupuk Guano - Dwi Erwin Kusbianto; Laura Yohana Sitompul; Ayu Puspita Sari; Bimantara Suryaridya Oetama (Berkala Ilmiah Pertanian, 2023)
There are 83 paper mills in Indonesia recorded by the Indonesian Pulp and Paper Association (APKI) spread throughout the archipelago. These paper companies produce products in the form of tissues, various types of paper, and other fiber-based products. Efforts to meet the needs of this raw material produce innovations in the form of using waste paper by separating the ink from the fibers contained in the paper, this separation process is known as the deinking process. Paper mill solid waste can be in the form of sludge, pith, and biosludge. Sludge is a factory solid waste originating from the settling of WWTP which consists of 90% solid and 10% liquid. Paper mill waste in the form of solid waste from sludge contains heavy metals such as Cd, Cr, Pb, Ni, Cu, and Zn. These metals can be overcome by bioremediation using guano fertilizer which is an organic material derived from bat droppings which is rich in phosphate. The purpose of this study was to determine the microbial population in soil contaminated with paper mill sludge waste treated with guano fertilizer. The parameters observed in this study were the total number of bacteria and fungi that survive in soil contaminated with paper mill waste as an indication that the land can still be planted with certain plants. This research was conducted at the Laboratory of Soil Biology, Laboratory of Soil and Land Fertility Agrotechnopark – Faculty of Agriculture – University of Jember. This study used a 3x3 two factorial experimental design with the basic pattern of Randomized Block Design (RAK), namely between the concentration of paper mill effluent and the dose of guano fertilizer, each treatment was repeated three times. The microbial population can be determined by analyzing total bacteria, total fungi. Soil that had been contaminated with paper mill waste was incubated with guano fertilizer, each combination was analyzed at 15 hst and 30 hst for total bacterial and total fungal populations. During the incubation period, irrigation was carried out using a sprayer to maintain moisture in the incubation media. The results showed that the total population of bacteria and fungi in the growing media contaminated with paper mill sludge waste by administering different doses of guano showed results that were not significantly different, but the total population tended to increase. with increasing incubation period. Pollution of sludge waste in the planting medium has a significant effect on increasing the total Fungi Population when compared to the control. The relationship between paper mill effluent pollution and guano fertilization is very low with a coefficient of determination of less than 0.5.